Conceptualizing condominium law and children: Comparing the state of strata titles law in New South Wales and Singapore - TANG, Hang Wu (Institutional Knowledge at Singapore Management University, 2023)
Purpose: This article conceptualises the legal relations embedded within condominium housing and the various theories of property ownership to ascertain how children’s interest fit within this framework. The laws of two jurisdictions, New South Wales and Singapore are examined to determine how their strata law responds when children’s safety is at stake. Design/methodology/approach: A comparative method using case law, statutes and secondary literature across both jurisdictions is adopted. This article also draws on various theories of property ownership. Findings: Drawing on pluralist moral theories of property law, the thesis advanced is that children’s issues within condominiums should not be subject to majoritarian rule especially when their safety is at stake. The paramount guiding value should be ensuring their safety within multi-owned housing communities. Using the law of two jurisdictions, New South Wales and Singapore, the central argument of this paper is that the law in these jurisdictions have rightfully adopted a protective approach towards children in multi-owned properties where their safety is at stake. Originality/value: The literature on the law of multi-owned housing has largely focused on governance issues such as mediating between the majority owners’ interest with that of the minority owners’ interest. Children in multi-owned developments remain an under investigated area as children’s interests do not fit within the paradigm of majority versus minority interests. The paper advances the argument that children’s interest should be viewed through either a rights-based theory or pluralists theories of property law. Lessons from the New South Wales and Singapore experience are also drawn which might prove useful to other jurisdictions.